Experimental investigation of condensation heat transfer and pressure drop of propane, R1234ze(E) and R22 in minichannels. (5th June 2016) - Liu, Na; Xiao, Hang; Li, Junming
Highlights: Condensation heat transfer and pressure gradients of propane and R1234ze(E) are investigated in minichannels. Effects of G, x, t s and channel geometry on h and (d p /d z )f are studied. h in a square tube is enhanced by the surface tension than in a circular tube. Propane and R1234ze(E) are good substitutes for R22 with good condensation heat transfer. Pressure gradients for propane and R1234ze(E) are larger than those for R22. Abstract: The paper reports measured heat transfer and pressure drop data for condensation of propane, R1234ze(E) and R22 in circular ( d h  = 1.085 mm) and square ( d h  = 0.952 mm) horizontal minichannels. The saturation temperatures are 40 °C and 50 °C with mass fluxes varying from 200 to 800 kg/(m 2  s) and vapor qualities from 0.1 to 0.9. The experiments investigated the effects of mass flux, vapor quality, saturation temperature and channel geometry on the heat transfer coefficients and pressure drops. The results show that the heat transfer coefficients and pressure drops increase with increasing mass flux and vapor quality and decreasing saturation temperature. The heat transfer coefficients in the square minichannel are larger than those in the circular minichannel. The study shows that propane and R1234ze(E) are good substitutes for R22 based on the condensation heat transfer characteristics. The pressure gradients in the circular and square minichannels differ little for propane with mass fluxes of 200, 350 and 500 kg/(m 2  s) and for R1234ze(E) with a mass flux of 500 kg/(m 2  s). The pressure gradients for propane are larger than those of R1234ze(E) which are larger than those of R22. Condensation heat transfer and two-phase pressure drop correlations were evaluated against the experimental data in the square minichannel.